Agroecological insights for Mandla, Madhya Pradesh, India: a contextual analysis for sustainable transformation - Malaiappan, Sudharsan; Krishnan, S.; Gadewar, P.; Sharma, H.; Priyadarshini, P.; Thakur, A.; Ganvir, S.; Acharya, P.; Kumar, Gopal; Shijagurumayum, M. S.; Singh, Sonali; Samaddar, A.; et al. (International Water Management Institute, 2024)
This report examines the agroecological, environmental, economic and social dimensions of Mandla district in Madhya Pradesh, India. Agroecological dimensions include recycling, input reduction, soil health, animal health, biodiversity, synergy, economic diversification, co-creation of knowledge, social values and diets, fairness, connectivity, land and natural resource governance, and participation. The report also highlights the challenges and opportunities for sustainable agroecological transformation.